1993
DOI: 10.1172/jci116797
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific expression of alpha 1-antitrypsin in human intestinal epithelium.

Abstract: show that a,-AT is also a product of Paneth cells. Together with the results of other studies, these data raise the possibility that a,-AT detected in fecal a,-AT clearance assays for diagnosing protein-losing enteropathies is predominantly derived from sloughed enterocytes. (J. Clin. Invest. 1993. 92:2022-2034

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 35 publications
(36 reference statements)
6
77
0
1
Order By: Relevance
“…Trypsin, also present as an inactive zymogen in Paneth cells, is believed to be the serine protease that converts proHD5 to the mature active form in the intestine (2,45). Although Caco2 cells produce trypsin, they also express ␣1-antitrypsin (47,48). Our finding of only proHD5, and not mature peptide, in the culture medium of cells treated with FGF9 is not surprising in view of their production of ␣1-antitrypsin and given the additional presence of serum ␣1-antitrypsin in the growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin, also present as an inactive zymogen in Paneth cells, is believed to be the serine protease that converts proHD5 to the mature active form in the intestine (2,45). Although Caco2 cells produce trypsin, they also express ␣1-antitrypsin (47,48). Our finding of only proHD5, and not mature peptide, in the culture medium of cells treated with FGF9 is not surprising in view of their production of ␣1-antitrypsin and given the additional presence of serum ␣1-antitrypsin in the growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…a1-PI is primarily a liver-derived serum protein with a molecular weight between 52 and 55 kDa. Recent studies showed that a1-PI is also synthesized outside the liver: by alveolar epithelial cells [3], monocytes [4], chondrocytes [5], human cornea [6] and, of importance for local control of inflammatory processes in the gut, in intestinal epithelial cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is produced predominantly by hepatocytes but also by blood monocytes, macrophages, pulmonary alveolar cells, and intestinal epithelial cells (20,21). The biological activity of AAT can be affected by point mutations modifying its structure and/or secretion.…”
mentioning
confidence: 99%